1999
DOI: 10.1590/s0104-79301999000100005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Lethal Factor From Opossum Serum Is a Potent Antidote for Animal, Plant and Bacterial Toxins

Abstract: Currently, the use of antivenoms is the only available treatment for envenomation caused by venomous animals namely, snake, scorpion, spider, tick and jelly fish. Antivenoms are generally produced in large animals, mostly in horses. A large percentage of the population is allergic to horse proteins. Several animals are known to be resistant to snakebites and the antihemorrhagic and anti-lethal components have been isolated from sera of opossum, mongoose, meerkat and hedgehog, as well as from venomous and non-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The object of this research is to provide a preparation consisting of a natural lethal toxin neutralizing factor (LTNF) derived from opossum serum that will serve as a relatively universal treatment for envenomation caused by animal, plant, and bacterial toxins (Lipps, 1999). Moreover, the use of LTNF will LTNF from Opossum Serum 83 prevent horse serum sickness.…”
Section: Animals Having Anti-hemorrhagic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The object of this research is to provide a preparation consisting of a natural lethal toxin neutralizing factor (LTNF) derived from opossum serum that will serve as a relatively universal treatment for envenomation caused by animal, plant, and bacterial toxins (Lipps, 1999). Moreover, the use of LTNF will LTNF from Opossum Serum 83 prevent horse serum sickness.…”
Section: Animals Having Anti-hemorrhagic Factorsmentioning
confidence: 99%
“…Peak number six contains the lethal toxin neutralizing factor. Reproduced from Lipps (1999) with permission of the publisher. Toxin Reviews Downloaded from informahealthcare.com by Gazi Univ.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the first 15 amino acids of the N‐terminal sequence of the full protein were found to contain the activity of the complete protein. Since the opossums are known to possess a natural protection from snake bites, LTNF was examined and shown to be capable of neutralizing the toxic effects of venom from various snakes, insects, plant and bacterial derived toxins . From a digest of the LTNF protein, researchers have reported that the N‐terminal portion (10–15 amino acids) of the protein maintained the potency of the full protein when administered to mice …”
Section: Introductionmentioning
confidence: 99%